2015
DOI: 10.1038/srep14036
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the protective effects of SYVN1 against diabetic retinopathy

Abstract: Genetic factors play an important role in the pathogenesis of diabetic retinopathy (DR). While many studies have focused on genes that increase susceptibility to DR, herein, we aimed to explore genes that confer DR resistance. Previously, we identified Hmg CoA reductase degradation protein 1 (SYVN1) as a putative DR protective gene via gene expression analysis. Transgenic mice overexpressing SYVN1 and wild-type (WT) mice with streptozotocin-induced diabetes were used in this experiment. Retinal damage and vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Synoviolin 1 (SYVN1) was associated with ER stress, chronic inflammation, and vascular overgrowth in diabetic retinopathy (DR) [37,38]. Overexpression of miR-125b-5p was associated with the pathogenesis of osteoarthritis by down-regulation of SYVN1 [38], reflecting that SYVN1 was closely associated with OA.…”
Section: Discussionmentioning
confidence: 99%
“…Synoviolin 1 (SYVN1) was associated with ER stress, chronic inflammation, and vascular overgrowth in diabetic retinopathy (DR) [37,38]. Overexpression of miR-125b-5p was associated with the pathogenesis of osteoarthritis by down-regulation of SYVN1 [38], reflecting that SYVN1 was closely associated with OA.…”
Section: Discussionmentioning
confidence: 99%
“…injection of streptozotocin (Sigma-Aldrich, St. Louis, MO), as previously described. 37 In the control group, a citric acid buffer solution was intraperitoneally injected into age-matched C57BL/6J mice. Follow-up tests showed that the blood glucose levels in diabetic mice were !16.7 mmol/L after 6 months.…”
Section: Animalsmentioning
confidence: 99%
“…Western blotting was performed as previously described. 37 Total protein was extracted from lysing mouse corneal epithelium samples and cultured TKE2 cells in radioimmunoprecipitation assay buffer. Protein quantification was performed using a kit (P0010; Beyotime Biotechnology, Beijing, China).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…MAOB (monoamine oxidase B) [249], VEGFC (vascular endothelial growth factor C) [250], DBP (D-box binding PAR bZIP transcription factor) [251], MYADM (myeloid associated differentiation marker) [252], NES (nestin) [253], SMURF1 [254], EDNRB (endothelin receptor type B) [255], MUC6 [256], TOR2A [257], TNKS (tankyrase) [258], NEDD9 [259], ASIC1 [260], ADAMTS8 [261], DYSF (dysferlin) [262], SLC26A9 [263], SLC45A3 [264] and KCNQ2 [265] contributes to the progression of hypertension, but these genes might be novel target for T1DM. Yang et al [266], Zhang et al [267] and Wang et al [268] demonstrated that SYVN1, BTG1 and CFB (complement factor B) were associated with diabetic retinopathy, but these genes might be novel target for T1DM.…”
Section: Discussionmentioning
confidence: 99%